2017
DOI: 10.1089/scd.2016.0331
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Migration and Proliferation Are Mediated by Hypoxia-Inducible Factor-1α Upstream of Notch and SUMO Pathways

Abstract: Mesenchymal stem cells (MSCs) are effective in treating several pathologies. We and others have demonstrated that hypoxia or hypoxia-inducible factor 1 alpha (HIF-1α) stabilization improves several MSC functions, including cell adhesion, migration, and proliferation, thereby increasing their therapeutic potential. To further explore the mechanisms induced by HIF-1α in MSCs, we studied its relationship with Notch signaling and observed that overexpression of HIF-1α in MSCs increased protein levels of the Notch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 51 publications
2
45
0
1
Order By: Relevance
“…Indeed, recent data have shown that increased SUMOylation is associated with increased pathotropism and proliferation of mesenchymal stem cells. 89 In stroke, transplanted stem cells have been shown to exert beneficial effects via structural replacement of damaged tissue and a litany of other immunomodulatory and neurotrophic actions. [90][91][92] Unfortunately, the clinical translation of such promising therapies continues to remain elusive, in part due to the limited persistence/survivability of grafted cells within the hostile ischemic microenvironment.…”
Section: Sumoylation and Stem Cellsmentioning
confidence: 99%
“…Indeed, recent data have shown that increased SUMOylation is associated with increased pathotropism and proliferation of mesenchymal stem cells. 89 In stroke, transplanted stem cells have been shown to exert beneficial effects via structural replacement of damaged tissue and a litany of other immunomodulatory and neurotrophic actions. [90][91][92] Unfortunately, the clinical translation of such promising therapies continues to remain elusive, in part due to the limited persistence/survivability of grafted cells within the hostile ischemic microenvironment.…”
Section: Sumoylation and Stem Cellsmentioning
confidence: 99%
“…Numerous attempts to restore the structure and function of the UB using the injection of MSCs suspension, as well as transplantation of various scaffolds seeded with stem cells, clearly demonstrated therapeutic efficacy (Coutu, Mahfouz, Loutochin, Galipeau, & Corcos, 2014;Kanematsu et al, 2005;Kim 2016; Lee et al, 2012). The main mechanisms of MSCs in reconstitution of bladder dysfunction were attributed to the cells migration, differentiation, and paracrine effects (Ciria et al, 2017;DeCoppi et al, 2007;Kanno et al, 2014). Recently, Lee et al reported that transplantation of human MSCs labelled with nanoparticles containing superparamagnetic iron oxide into the bladder inhibited bladder fibrosis and increased blood flow and decreased tissue hypoxia, which contributed to improvement in histopathological and functional parameters.…”
mentioning
confidence: 99%
“…The ASCs cultured both statically and dynamically under 2% O2 were also shown to express HIF-1α, consistent with hypoxia in adipose tissue being < 5% O2 59,60 . HIF-1α activation is associated with MSC proliferation 61,62 , which may have contributed to the enhanced Ki-67 expression in the hypoxic dynamic group. A previous study by Choi et al demonstrated that culturing human ASCs under 2% O2 increased proliferation relative to culture under ~21% O2 through HIF-1α-mediated mechanisms 26 .…”
Section: Dynamic Culture Methods Can Enhance Cell Proliferation and Imentioning
confidence: 99%